Stabilization of a Coupled Multidimensional System - Nicaise, Serge; Sene, Abdoulaye (Revista Matemática Complutense, 2006)
We introduce a model of a vibrating multidimensional structure made of a n-dimensional body and a one dimensional rod. We actually consider the anisotropic elastodynamic system in the n-dimensional body and the Euler-Bernouilli beam in the one-dimensional rod. These equations are coupled via their boundaries. Using appropriate feedbacks on a part of the boundary we show the exponential decay of the energy of the system.